Hepatoprotective Effects of Avicennia Marina (Forssk.) Vierh. - Omid Farshad; Reza Heidari; Hamidreza Mohammadi; Amin Reza Akbarizadeh; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2017)
The xenobiotics-induced liver injury is a major clinical complication. Hence, finding hepatoprotective agents could have clinical value. Herbal medicines are a major source of biologically active chemicals which could be applied as hepatoprotective agents. The current study was designed to assess the hepatoprotective properties of Avicennia Marina (AM) extract and its different fractions. In vivo, the hepatoprotective effect of AM total extract against CCl4-induced acute liver injury was evaluated in rats, and a series of histopathological, biochemical, and oxidative stress parameters were monitored. In vitro, the protective effect of AM extract fractions (Petroleum ether, Chloroform, Ethyl acetate, and Ethanol) was evaluated on human liver hepatoma cells (HepG2). Severe elevation in serum level of liver injury biomarkers, along with liver tissue histopathological changes, lipid peroxidation, and liver tissue glutathione depletion were detected in CCl4-treated rats. On the other hand, CCl4-induced toxicity was evident in vitro by significant cell death. It was found that AM extract provided significant protection against CCL4 toxicity in vivo by decreasing serum biomarkers of liver injury and tissue markers of oxidative stress. In vitro, the protective effect of AM extract fractions (Chloroform, Ethyl acetate, and Ethanol) was evident as these fractions significantly decreased CCl4 cytotoxicity. As AM extract exhibited significant suppression of oxidative stress markers, its antioxidant effect could play a significant role in its hepatoprotective properties.